Estimating cost efficiency of Turkish commercial banks under unobserved heterogeneity with stochastic frontier models - Hakan Gunes; Dilem Yildirim (Central Bank Review (CBR), 2016)
This study aims to investigate the cost efficiency of Turkish commercial banks over the restructuring period of the Turkish banking system, which coincides with the 2008 financial global crisis and the 2010 European sovereign debt crisis. To this end, within the stochastic frontier framework, we employ true fixed effects model, where the unobserved bank heterogeneity is integrated in the inefficiency distribution at a mean level. To select the cost function with the most appropriate inefficiency correlates, we first adopt a search algorithm and then utilize the model averaging approach to verify that our results are not exposed to model selection bias. Overall, our empirical results reveal that cost efficiencies of Turkish banks have improved over time, with the effects of the 2008 and 2010 crises remaining rather limited. Furthermore, not only the cost efficiency scores but also impacts of the crises on those scores appear to vary with regard to bank size and ownership structure, in accordance with much of the existing literature.
Keywords: C23; C24; D21; G21; G28; 330; Stochastic frontier; Cost efficiency; Turkish commercial banks; Panel data; Unobserved heterogeneity; True fixed effects; Model uncertainty; Model-averaged efficiency